Philosophy and Modernity - Cloots, André (Archīum Ateneo, 2024)
What can still be the meaning of philosophy in modernity? The core of modernity is “liberty, equality, and fraternity through rationality.” The last element, viz. rationality, however, implies that modernity is at once a critical analysis of its own core. Reason is intrinsically linked to critique, even to a critique of modernity’s own basics, including its rationality. Therefore, modernity is not something ‘substantial’ but rather a process. Nor is it a matter of reducing everything to the same – the same of reason; but on the contrary, it is a new way of dealing with plurality. This affects also the status of philosophy and its relation to the plurality of other independent forms of insight, like science, art, religion, etc. Philosophy can no longer provide the ultimate foundation for all the rest (at the bottom – Descartes) nor can it be any longer its all integrating absolute knowledge (at the top – Hegel). Lyotard describes philosophy as only a small vessel. But that does not diminish its central role in today’s modernity.